(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2024)
The supply chain (SC) is a fundamental aspect for management and operational efficiency in all stages of agricultural production. Adequate characterization of the SC guarantees the coordinated integration of each link in the process. The objective of this research was to characterize the vegetable supply chain in the department of Boyacá-Colombia. Through a literature review and following the methodology described by García (2006), we identified the current state of the SC, its main links, functioning, problems, as well as its productive and innovation potential. productive and innovation potential. The results showed that vegetable production has experienced considerable growth in recent years, with products such as onions, carrots and tomatoes being those with the highest production at the regional level. production at the regional level. The production of these vegetables shows a low degree of technification; however, transportation logistics, storage and handling are the operations with the greatest impact on the quality of vegetable products and the generation of waste. Therefore, the adoption of good agricultural practices and cold storage mechanisms are suggested as potential opportunities for the growth of the country’s horticultural sector.